2023
DOI: 10.1002/cpt.2908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Hepatitis C on the Activity of the Membrane Transporters P‐gp and OATP1B1/BCRP on Patients With Different Stages of Hepatic Fibrosis

Abstract: The activity of the membrane transporters organic anion-transporting polypeptide 1B1 (OATP1B1) & breast cancer resistance protein (BCRP) (rosuvastatin) and P-glycoprotein (P-gp) (fexofenadine) was evaluated in patients with chronic hepatitis C virus (HCV) infection (n = 28), genotypes 1 and 3, investigated before the treatment with directacting antiviral agents (Phase 1) and up to 30 days after the assessment of the virologic response (Phase 2). Participants allocated in Groups 1 (n = 15; F0/F1 and F2, mild to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…However, these studies have not mimicked the physiological inflammatory conditions in humans, making it difficult to translate the findings to changes in the in vivo pharmacokinetics (PK) of drugs in humans. Studies from this research group have reported that systemic inflammation resulting from rheumatoid arthritis, systemic lupus erythematosus, visceral leishmaniasis, and chronic hepatitis C alters the activity of CYP enzymes and hepatic/intestinal drug transporters [4][5][6][7][8]. However, to date, have been no studies on the impact of inflammation on the in vivo activities of the renal transporters, especially during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies have not mimicked the physiological inflammatory conditions in humans, making it difficult to translate the findings to changes in the in vivo pharmacokinetics (PK) of drugs in humans. Studies from this research group have reported that systemic inflammation resulting from rheumatoid arthritis, systemic lupus erythematosus, visceral leishmaniasis, and chronic hepatitis C alters the activity of CYP enzymes and hepatic/intestinal drug transporters [4][5][6][7][8]. However, to date, have been no studies on the impact of inflammation on the in vivo activities of the renal transporters, especially during pregnancy.…”
Section: Introductionmentioning
confidence: 99%